Lipid Profile as a Predictor of HbA1c in Women with Gestational Diabetes Mellitus - Amirah , Amirah; Yudistira , Yudistira; Arlitha Deka Yana (Community Medicine and Education Journal, 2024)
Gestational diabetes mellitus (GDM) is associated with adverse maternal and fetal outcomes. While glycemic control is paramount, the role of lipid profiles in predicting HbA1c levels, a marker of long-term glycemic control, remains under-investigated in Indonesian populations. This observational study enrolled 250 women diagnosed with GDM at the primary healthcare centers in Soppeng Regency. Fasting lipid profiles (total cholesterol, triglycerides, LDL-cholesterol, HDL-cholesterol) and HbA1c levels were measured at diagnosis and at 24-28 weeks gestation. Statistical analyses included correlations, regression models, and receiver operating characteristic (ROC) curve analysis. HbA1c levels were significantly correlated with triglyceride and LDL-cholesterol levels at both time points. Regression analysis revealed that triglycerides were the strongest independent predictor of HbA1c. ROC curve analysis showed moderate discriminatory power for triglycerides in predicting elevated HbA1c (AUC 0.72). Lipid profiles, particularly triglycerides, may serve as early predictors of HbA1c levels in women with GDM. These findings underscore the importance of monitoring lipid profiles alongside glucose control in this population.